Genetic variation of IRF6 and TGFA genes in an HIV‐exposed newborn with non‐syndromic cleft lip palate. (30th August 2020) - Sufiawati, Irna; Maskoen, Ani Melani; Soemantri, Eky Setiawan Soeria
Abstract: We present here the first reported case of a non‐syndromic cleft lip and palate (NSCLP) in an HIV‐exposed newborn of a mother on antiretroviral therapy (ART) in Indonesia. Genetic testing was performed to confirm a suspected genetic condition. Genomic DNA was extracted from the blood, and genetic variations of the interferon regulatory factor 6 ( IRF 6) rs642961 (Mspl) (G>A) and transforming growth factor alpha ( TGFA ) Bam HI (rs11466297, A>C) and Rsa I (rs3732248, C>T) were performed by PCR‐RFLP and IRF 6 gene analysis by PCR sequencing. Genotyping of DNA sequence variants in the IRF 6 gene showed both parents had genotype GA, while the child had genotype GG (genotype wild type). There was no difference observed in the TGFA Bam HI gene variant between the child and her mother and father that were wild‐type polymorphisms (normal), while the Rsa 1 polymorphisms of them were heterozygotes. A genetic variant of IRF 6 might be a protective factor for NSCLP, while Rsa 1 gene variant (A) allele can be considered to be the risk factor associated with NSCLP development. This case report also highlights the possible etiologic role of ART in NSCLP; therefore, early control of adverse effects of ART might be an important factor in decreasing the incidence of the congenital anomalies in HIV‐infected children.